Frequency-dependent ERK phosphorylation in spinal neurons by electric stimulation of the sciatic nerve and the role in electrophysiological activity - Wang Shenglan; Kobayashi Kimiko; Obata Koichi; Yamanaka Hiroki; Kamo Hiroshi; Iwata Koichi; Dai Yi; Fukui Tomokazu; Cui Xiuyu; Yoshiya Shinichi; Noguchi Koichi (SAGE Publishing, 2007)
Abstract The phosphorylation of extracellular signal-regulated kinase (pERK) in DRG and dorsal horn neurons is induced by the C-fiber electrical stimulation to the peripheral nerve. The present study was designed to investigate the expression and modulation of pERK in the rat dorsal horn neurons produced by repetitive electrical stimulation, and its involvement in the electrophysiological activity of dorsal horn neurons. Electrical stimulation of C-fiber intensity at different frequencies was applied to the sciatic nerve; the stimuli-induced pERK expression and the activity in dorsal horn neurons were studied by immunohistochemistry and extracellular recording, respectively. Electrical stimulation of C-fibers (3 mA) induced pERK expression in dorsal horn neurons in a frequency-dependent manner, indicating that the frequency of electrical stimulation is an important factor which activates the intracellular signal pathway in the spinal cord. To demonstrate the underlying mechanism of this frequency-dependent pERK expression, an NMDA receptor antagonist, MK-801, and a voltage sensitive calcium channel antagonist, nifedipine, were administrated intrathecally before the stimulation. We found that high frequency (0.5 Hz and 10 Hz) but not low frequent (0.05 Hz) stimulus-evoked pERK was partially inhibited by MK-801. Both high and low frequency stimulus-evoked pERK were inhibited by the nifedipine treatment. The extracellular single unit activities were recorded from the laminae I-II and V of the L4-5 dorsal horn, and we found that blockage of the intracellular ERK signal suppressed the wind-up responses in a dose-dependent manner. In contrast, any change in the mechanically evoked responses was not observed following the administration of ERK inhibitor. These observations indicate that ERK activation plays an important role in the induction of the wind-up responses in dorsal horn nociceptive neurons.